2022
DOI: 10.1073/pnas.2117054119
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis and molecular mechanism of biased GPBAR signaling in regulating NSCLC cell growth via YAP activity

Abstract: The G protein–coupled bile acid receptor (GPBAR) is the membrane receptor for bile acids and a driving force of the liver–bile acid–microbiota–organ axis to regulate metabolism and other pathophysiological processes. Although GPBAR is an important therapeutic target for a spectrum of metabolic and neurodegenerative diseases, its activation has also been found to be linked to carcinogenesis, leading to potential side effects. Here, via functional screening, we found that two specific GPBAR agonists, R399 and IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…The GPBAR is highly expressed in non-small cell lung cancer (NSCLC), and a positive correlation exists between GPBAR expression levels and the clinical progression of NSCLC (Liu et al, 2018). Ma et al (Ma et al, 2022) recently identified a novel GPBAR agonist, R399, that preferentially promotes βarr1 signaling. Studies with NSCLC cells showed that R399 stimulated YAP signaling and cell proliferation in a βarr1-dependent fashion (Ma et al, 2022).…”
Section: Medulloblastoma Medulloblastoma (Mb) Is the Most Common Pedi...mentioning
confidence: 99%
See 2 more Smart Citations
“…The GPBAR is highly expressed in non-small cell lung cancer (NSCLC), and a positive correlation exists between GPBAR expression levels and the clinical progression of NSCLC (Liu et al, 2018). Ma et al (Ma et al, 2022) recently identified a novel GPBAR agonist, R399, that preferentially promotes βarr1 signaling. Studies with NSCLC cells showed that R399 stimulated YAP signaling and cell proliferation in a βarr1-dependent fashion (Ma et al, 2022).…”
Section: Medulloblastoma Medulloblastoma (Mb) Is the Most Common Pedi...mentioning
confidence: 99%
“…Ma et al (Ma et al, 2022) recently identified a novel GPBAR agonist, R399, that preferentially promotes βarr1 signaling. Studies with NSCLC cells showed that R399 stimulated YAP signaling and cell proliferation in a βarr1-dependent fashion (Ma et al, 2022). In contrast, treatment of NSCLC cells with a G protein-biased GPBAR agonist, INT-777, interfered with YAP signaling, inhibited cell proliferation, and induced apoptosis (Ma et al, 2022).…”
Section: Medulloblastoma Medulloblastoma (Mb) Is the Most Common Pedi...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when complexing with INT-777, which is also an agonist, priority is given to activating GPBAR-Gs signalling, inhibiting cell proliferation and inducing apoptosis. The reason for this difference is that different ligands have different complexed residual sites with TGR5, which leads to biased activation of the signal 32 . Unexpectedly, the study found that there is a second ligand-binding cavity in TGR5.…”
Section: The Bile Acid Receptor Tgr5mentioning
confidence: 99%
“…[16] G protein-coupled bile acid receptor activation can control YAP activity and regulate distinct functions of cell growth and apoptosis. [20] Therefore, we hypothesized that GRK2, a regulator of GPCR, modulated the YAP signaling and contributed to PAH in mice and humans.…”
Section: Introductionmentioning
confidence: 99%